Penerapan Akuntansi Lingkungan Terhadap Keberlanjutan Menggunakan Perspektif Pentuple Bottom Lines Pada PG. Modjopanggoong - Salsa Amalia Maghfiroh (CV. Ulil Albab Corp, 2025)
This study aims to determine how the application of the environmental accounting to sustainability using the perspective of the pentuple bottom lines and to determine how PG. Modjopanggoong overcomes the challenges and obstacles faced in the application of environmental accounting to the sustainability using the perspective of the pentuple bottom lines. This study uses a qualitative descriptive method with a pentuple bottom lines perspective which includes five aspects, namely people, profit, planet, prophet, and phenotechnology. The results of the study indicate that in the application which since from